Serum zinc levels of hospitalized children with acute diarrhea differ by the isolated viruses - Afolabi, Oyetundun F. (Int J Health Sci (Qassim), 2019)
BACKGROUND: Acute diarrhea constitutes a major global burden to morbidity and mortality in under-five children. Research has shown that micronutrient zinc plays a pivotal role in childhood diarrhea; however, there are contradictory reports of its therapeutic benefit across the various causative enteropathogens. OBJECTIVES: The aim of the study was to determine the prevalence of viral etiology (rotavirus, adenovirus, and norovirus) and compare the serum zinc levels of children with acute diarrhea. METHODS: A comparative cross-sectional study in which 100 hospitalized children with acute diarrhea aged one–59 months and 100 controls were recruited. Viruses were investigated from stool specimens using the immunochromatographic technique, while serum zinc was determined through the colorimetric method. Data analysis was with SPSS 20 software package. RESULTS: The prevalence of viruses in the subjects was 62.0% with rotavirus isolated in 30 (30.0%) of the patients, while adenovirus and norovirus were detected in 21 (21.0%) and 11 (11.0%) patients, respectively. Rotavirus was the only virus detected in 2 (2.0%) of the controls. The mean serum zinc level of 65.3 ± 7.4 µg/dl in the subjects was significantly lower than 69.0 ± 6.5µg/dl in the controls (P < 0.001). The prevalence of zinc deficiency in the subjects (47.0%) was significantly higher than 32.0% in the controls (P = 0.030). The mean serum zinc levels differed significantly among the viruses isolated in the subjects (P < 0.001). CONCLUSIONS: Viruses contribute largely to etiology of acute diarrhea in Nigerian under-five children. Zinc deficiency was also highly prevalent in the study population. The serum zinc levels varied significantly across the different viruses isolated.